Injertos óseos - Nueva alternativa. Fase II. Evaluación de las propiedades osteoinductoras de las proteínas morfogenéticas óseas parcialmente purificadas, implantadas en tejido subcutáneo de un modelo experimental lapino (2003)
ABSTRACT: The purpose of this research was to evaluate the osteoinductive characteristics of partially purified bone morphogenetic proteins from bovine bone, through subcutaneous implantation in an experimental lapin model, to be used later as bone graft material mixed with an osteoconductive material. The procedure was carried out through subcutaneous implantation of 8 mg of BMP in the dorsal region at scapula level, in 21 New Zealand rabbits. They were distributed into 6 evaluation groups at 3,6,9,12,21 days and 8 weeks of evolution, when the implants were removed and sent to histopatologic evaluation through convencional optic microscopy to characterize different tissue elements, that included bone neoformation. The results were analyzed with multiple correspondence factorial method with jerarquic classification, and showed that BMP stimulate bone induction in ectopic sites, having osteogenic activity, because osseous trabeculae were noticed in all samples taken since day 6 post implantation.